Invariances of the Operator Properties of Frame Multipliers Under Perturbations of Frames and Symbol. (4th April 2018) - Javanshiri, Hossein
ABSTRACT: Let Φ and Ψ be frames for ℋ and let M m, Φ, Ψ be a frame multiplier with the symbol m . In this paper, we restrict our investigation to show that the operator properties of M m, Φ, Ψ are stable under the perturbations of Φ, Ψ, and m . Also, special attention is devoted to the study of invertible frame multipliers.